The Role of Islamic Boarding Schools in Strengthening the Tauhid Values of Students - Ade Saepudin; Mulyanto (Didaktika: Jurnal Kependidikan, 2025)
Islamic educational institutions in Indonesia, such as families, schools, and Islamic boarding schools, have an important role in conveying Islamic teachings. Islamic religious education plays an important role in shaping the character and morals of the Muslim generation. This education not only aims to provide an understanding of religious knowledge, but also to instill noble morals and strengthen faith. This study aims to examine the role of Tauhid education in shaping the character of students in Islamic boarding schools, with a focus on teaching Tauhid through traditional methods and classical text-based curriculum. The research method used is a literature study, analyzing various sources related to the teaching of Tauhid in Islamic boarding schools, including classical books that are the main references in Islamic religious education. The research findings show that Tauhid education in Islamic boarding schools has a significant impact on strengthening the understanding of faith and shaping students into individuals who are devout, have noble morals, and have deep spirituality. The teaching of Tauhid through classical texts, such as the Book of Al-Tauhid, and its direct application in structured worship practices has proven effective in internalizing the values ​​of Tauhid in everyday life. Traditional teaching methods, such as sorogan and bandongan, have proven to be effective tools for deepening practical understanding of tauhid. The practical implications of these findings suggest that pesantren can serve as an effective educational model for maintaining the purity of Islamic faith, preventing doctrinal deviations, and equipping the younger generation with a comprehensive understanding of religion.